Goodnight moon - Brown, Margaret Wise 1910-1952; Hurd, Clement 1908-1988 (New York, NY Scholastic, Inc., 1975)
A little bunny bids goodnight to all the objects in his room before falling asleep in this story in rhyme.
Keywords: Children's literature